(untitled) (Research, Society and Development, 2023)
Aging is an inevitable result of life, characterized by a progressive decline in the function of tissues and organs and an increased risk of mortality. Along with the increase in the elderly population, observed in recent years, there is an increase in the prevalence of neurodegenerative diseases, such as Alzheimer’s Disease (AD). The present study consists of an integrative literature review in order to identify the influence of genetic and epigenetic factors in the pathogenesis of AD. The search was carried out during the months of September, October and November 2022, considering studies published in the period between 2014 and 2022, in the following databases: VHL, PubMed MEDLINE, SCIELO, Google Scholar and EbscoHost. It is now very clear that all characteristics of an individual are not determined by DNA alone, but by environment, stress, lifestyle and nutrition that play a vital role in determining an organism’s response. In this sense, epigenetic mechanisms involve structural and biochemical changes in chromatin, without alterations in the DNA sequence, which disfigure the expression pattern of genes, affecting several physiological and pathological processes. Therefore, this imbalance in the homeostasis of epigenetic mechanisms is the basis for the abnormal expression of genes related to synaptic plasticity and memory, areas that are notably altered in the initial manifestations of AD. Given the reversible nature of epigenetic mechanisms, these pathways provide promising avenues for therapy against cognitive decline and better prognosis for the disease.